The Functional Evaluation of Eating Difficulties Scale: Study Protocol and Validation in Infants with Neurodevelopmental Impairments and Disabilities - Cavallini, Anna; Provenzi, Livio; Sacchi, Daniela; Longoni, Laura; Borgatti, Renato (Frontiers in Pediatrics, 2017)
Introduction: A reliable and accurate evaluation of oral-motor skills in newborns at risk for swallowing and feeding disorders is key to set the goals of effective early interventions. Although many tools are available to assess oral-motor skills in newborns, limited evidence exists for what pertains their reliability and their effectivity in predicting short- and long-term developmental outcomes in at-risk infants. The aim of the present study is to develop and provide a preliminary validation of a new clinically-grounded tool (i.e., the Functional Evaluation of Eating Difficulties Scale, FEEDS) specifically designed to be used with at-risk newborns and infants. The paper describes the steps of tool development and information on the reliability of the tool are provided. Methods/analysis: The FEEDS has been developed according to clinical evidence and expertise by a multi-disciplinary team of professionals dealing with feeding problems in at-risk infants diagnosed with neurodevelopmental impairments and disabilities. The steps of FEEDS development are reported, together with a detailed description of items, scoring procedure and clinical cut-off. The FEEDS has been applied to a relatively large sample of 0-to-12-month-old infants (N = 136) with neurodevelopmental disability, enrolled consecutively between 2004 and 2016 at the Scientific Institute IRCCS Eugenio Medea (Bosisio Parini, Italy), which is the main rehabilitation hospital for children with neurodevelopmental disabilities in Italy. Internal consistency (Cronbach’s alpha) and reliability (inter-rater agreement) have been assessed. Ethics and dissemination: All the procedures are consistent with the World Medical Association Declaration of Helsinki (2013) and the FEEDS has been approved by the clinical committee of the Scientific Institute IRCCS Eugenio Medea. Further psychometric characteristics and evidence of the predictive validity of the FEEDS will be obtained on a larger sample and they will be reported in future publications from this group.